Poly(sulfobetaine methacrylate)/poly(ethylene glycol) hydrogels for chronic wounds management. (August 2019) - Ruseva, Konstans; Ivanova, Kristina; Todorova, Katerina; Gabrashanska, Margarita; Hinojosa-Caballero, Dolores; Tzanov, Tzanko; Vassileva, Elena
Graphical abstract: Highlights: Temperature and salt-responsive polymeric materials. Able to absorb wound exudate which makes them very appropriate for highly exuding wounds treatment. Able to control the enzymes concentration in the chronic wounds through absorption without inhibiting their activity. Exhibiting antibiofilm activity against S. aureus - bacteria, which is common for chronic wounds. Non-cytotoxic and with very good tolerance by the surrounding tissues as revealed by in vivo experiments. Abstract: Polyzwitterions (PZI) recently emerged as biomaterials with excellent bio- and haemo-compatibility, demonstrating lower protein adsorption on their surfaces even compared to the golden standard in the field – poly(ethylene glycol) (PEG). Although PZI combine many beneficial for chronic wound treatment properties as nonfouling ability and high capacity to absorb wound exudate, their potential for such demanding application is still unrevealed. In this work, polysulfobetaine (PSB) networks were synthesized using PEG-based crosslinking agent, thus combining in one material two polymers with inherent antifouling properties. The obtained PSB hydrogels demonstrate linear temperature dependence of their swelling capacity in water between 20 and 70 °C. Moreover, they all exhibit strong antipolyelelctrolyte behavior, increasing their swelling ratio between 10 and 22 times depending on their crosslinking degree as the NaCl concentration increased. The study also demonstrates the PSB high ability to bind water - ∼40% bound water was determined for almost all PSB hydrogels, which is considered as the main reason for their ultra-low non-specific protein binding ability. Moreover, PZI networks effectively absorb and retain the major enzymes causing chronicity of the wounds as 30–40% myeloperoxidase (MPO) was loaded into the PSB hydrogels depending on their crosslinking degree. At the same time, PZI hydrogels do not inhibit neither MPO nor the collagenase activity, thus ensuring a decrease in their excessive amount in the chronic wounds but at the same not hampering the enzyme activity necessary for the proper wound healing. All PSB hydrogels demonstrated antibiofilm activity against S. aureus, a common bacterial representative in chronic wounds. The non-cytotoxicity and biocompatibility of the hydrogels were proved in vitro and in vivo . Thus, the study demonstrated the PSB hydrogels' advantages as dressing materials for chronic wound healing, namely: (i) high ability to absorb wound exudate; (ii) high ability to bind water; (iii) good control on the enzymes concentration in the chronic wounds through absorption (iv) without inhibiting their activity; (v) antibiofilm activity against common for the chronic wounds bacteria; (vi) non-cytotoxicity and (vii) in vivo proved very good tolerance by the surrounding tissues.